Modal birefringence of slotted silica waveguide in photonic crystal fiber using comsol multiphysics / Nurul Nadia Sarif - Sarif, Nurul Nadia (2013)
The project modal birefringence of slotted silica waveguide is an investigation on the effect of the number of waveguide slabs in slotted silica waveguide with the effective index that will be produced. The large difference in the effective index will produce a mall and compact multimode interference device. The slotted silica waveguide is rectangular in shape. The simulation was done by using the COMSOL Multiphysics software. The refractive index of silica glass used is 1.444 while the refractive index for air is 1.0. The wavelength of the light used in the simulations is 1.55um. The value of effective index mode is taken from a various number of the slab in the waveguide which is 1,3,5,7, and 9. Then, the difference in effective index modal birefringence is determined. The simulation is conducted to investigate the effect of width and height of slab silica glass in the modal indices. The difference in effective indices of the modes wave is determined and compared to find the most suitable structure that gives the largest modal birefringence thus producing a small and compact multimode interference device.